Samuel Adams – Greg Schmidt Goering – Matthew J. Goff (eds.), Sirach and Its Contexts. The Pursuit of Wisdom and Human Flourishing (Supplements to the Journal for the Study of Judaism 196; Leiden – Boston, MA: Brill 2021) - Zieliński, Marcin (The Biblical Annals, 2023)
Book Review: Samuel Adams – Greg Schmidt Goering – Matthew J. Goff (eds.), Sirach and Its Contexts. The Pursuit of Wisdom and Human Flourishing (Supplements to the Journal for the Study of Judaism 196; Leiden – Boston, MA: Brill 2021). Pp. 301. € 125. ISBN: 978-90-04-44733-2 (E-Book).